The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1179/1743282012y.0000000008
|View full text |Cite
|
Sign up to set email alerts
|

Haplocladium microphyllum(Hedw.) Broth. capsules as food forAgrotissp. (Lepidoptera) larvae

Abstract: Bryophytes usually have anti-feeding properties to defend against microbial and herbivore attack; however, the consumption of Haplocladium microphyllum (Hedw.) Broth. capsules by Agrotis sp. larvae is rather common in Shanghai in the spring. To test whether H. microphyllum is the only moss eaten, and why the gametophytes of H. microphyllum are not eaten, a series of quantitative experiments were carried out to understand the feeding habits of Agrotis larvae on the given moss materials at three growth stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Liao (1993) reported that the phenolic content of capsules (25 mgÁg À1 fresh weight) is lower than that of shoots (82 mgÁg À1 fresh weight) in Funaria hygrometrica. Field studies found that sporophytes were eaten more frequently than gametophytes, which may be attributed to a reduction in defences during the breeding season (Davidson et al 1990;Fang & Zhu 2012). This conclusion is based on the difference in constitutive defence between sporophytes and gametophytes (Davidson et al 1990;Liao 1993;Fang & Zhu 2012), while ignoring the induced defence.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Liao (1993) reported that the phenolic content of capsules (25 mgÁg À1 fresh weight) is lower than that of shoots (82 mgÁg À1 fresh weight) in Funaria hygrometrica. Field studies found that sporophytes were eaten more frequently than gametophytes, which may be attributed to a reduction in defences during the breeding season (Davidson et al 1990;Fang & Zhu 2012). This conclusion is based on the difference in constitutive defence between sporophytes and gametophytes (Davidson et al 1990;Liao 1993;Fang & Zhu 2012), while ignoring the induced defence.…”
Section: Introductionmentioning
confidence: 99%
“…Field studies found that sporophytes were eaten more frequently than gametophytes, which may be attributed to a reduction in defences during the breeding season (Davidson et al . 1990; Fang & Zhu 2012). This conclusion is based on the difference in constitutive defence between sporophytes and gametophytes (Davidson et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1964, Ehrlich and Raven stated that among herbivorous lepidopteran larvae, none is known to feed on bryophytes, nor on ferns, before mentioning the fern eaters Papaipema moths (Noctuidae; see page 598 in Ehrlich & Raven, 1964 ). Years later, studies on early land plants reported that various herbivores, including mammals, birds, gastropods, and arthropods can actually feed on bryophytes (Davidson et al, 1990 ; Fang & Zhu, 2013 ; Glime, 2017 ; Maciel‐Silva & Santos, 2011 ; Singer & Mallet, 1986 ) and pteridophytes (Hamm & Fordyce, 2016 ; Schneider, 2016 ). Some insects have even been shown to specialize on mosses, like weevils from the tribe Ectemnorhinini (Coleoptera: Curculionidae; Chown, 1990 ), larvae of some snipe flies (Diptera: Rhagionidae; Imada & Kato, 2016 ), or crane flies species (Diptera: Tipulidae; Freeman, 1967 ).…”
Section: Introductionmentioning
confidence: 99%